Dynamic stability analysis for rotating pre-twisted FG-CNTRC beams with geometric imperfections restrained by an elastic root in thermal environment. (July 2021) - Lin, Baichuan; Chen, Bo; Zhu, Bo; Li, Ji-an; Li, Yinghui
Abstract: This paper deals with the problems of free vibration, buckling, and dynamic stability of rotating pre-twisted functionally graded carbon nanotube reinforced composite (FG-CNTRC) imperfect beams in thermal environment. The imperfect beam contains different modes of geometric imperfections such as sine, global, and local modes, and it is restrained by an elastic root. Three types of CNTs distributions including FG-X, UD, and FG-O distributions are considered and the material is temperature-dependent. First, bending–bending coupled governing equations are established through the Hamilton's principle based on the Euler–Bernoulli beam theory. By setting different parameters, the governing equations can solve the problems of free vibration, buckling, and dynamic stability of the beam. Then, the differential quadrature method (DQM) is employed to get the discrete equations and numerical solutions of the natural frequency, critical buckling load, and instability region. Finally, parametric studies are carried out to present the effects of hub radius, rotating speed, material properties, geometric imperfections, and rigidity of the elastic root on the natural frequencies, critical buckling load, and instability regions. Results show that the elastic root and imperfection mode have obvious influence on the instability regions. Highlights: Dynamic stability of geometrically imperfect rotating pre-twisted FG-CNTRC beams is investigated. Influence of elastic root on the critical load and instability regions are investigated. Imperfection sensitivity of instability regions to various imperfection modes is studied. Studying the effects of temperature-dependence of material properties. Using the differential quadrature method to deal with elastic boundary conditions.